Teologika Kepemimpinan Pelayanan Konstrutif - Yudhi Kawangung (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2021)
Leadership in the title describes the attitudes and abilities of a person who is selected with competence and Christian character based on theological studies, so as to be able to support constructive service fields. Nowadays the productivity review and leadership principles are often absent to fill the fundamentals that remain true to theological ground because of the wide range of experiential product offerings. However, the product is at a distance, then the equilibrium curve is inversely proportional and there is a weak understanding of the theological basis, so that it loses the authority and spiritual competency due to no longer relying on the Bible, as a result constructive service becomes sloping. This paper aims to systematically describe the capacities and capabilities of leadership in the context of constructive service to the people, so that the framework as well as the sketches that have been presented in this paper is able to answer the crisis and friction surrounding leadership. This research approach uses descriptive, literary and exegetical methods, which means explaining by investigating various related literatures and then analyzing it word for word to extract the hidden meanings of the text and context. Kepemimpinan dalam judul tersebut memaparkan tentang sikap dan skill seorang terpilih dengan kompetensi serta karakter kristiani yang berpijak pada kajian teologika, sehingga mampu mem’back-up’ untuk menunjang bidang layanan yang konstruktif. Dewasa ini produktivitas tinjauan dan kaidah kepemimpinan acapkali absen mengisi soal-soal fundamental yang tetap setia pada pijakan teologis oleh karena maraknya tawaran produk pengalaman. Akan tetapi produk tersebut berjarak yang kemudian kesetimbangan kurva berbanding terbalikdan terjadi adanya lemahnya pemahaman pijakan teologis.Sehingga kehilangan kewibawaan dan kewenangan spiritualitas disebabkan tidak bertumpu lagi pada Alkitab akibatnya pelayanan konstruktif melandai. Tulisan ini bertujuan untuk membentangkan secara sistematis akademis tentang kapasitas dan kapabilitas kepemimpinan dalam rangka pelayanan konstruktif kepada umat. Sehingga kerangka sekaligus sketsa yang sudah disuguhkan dalam tulisan ini mampu menjawab krisis dan friksi seputar kepemimpinan. Pendekatan riset ini dengan metoda deskriptif, pustaka dan eksegesa yang artinya memaparkan dengan menyelidiki berbagai literatur terkait kemudian ditelaah kata demi kata untuk mengeluarkan makna tersembunyi dari teks dan konteks.